Pelatihan Online Content Marketing dan Desain Bagi Pemula Dengan Menggunakan Aplikasi Canva - Adi Darmawan; Laksamana, Patria; Saripudin; Suharyanto (Jurnal Abdimas Perbanas, 2022)
Graphic design and marketing content are two important things in both conventional and digital marketing activities. A good quality of design and content is needed, not only from the aspect of content, design and visual appearance, but also to several other aspects, namely concepts, trends, market segments, costs, and including the applications used. The Canva Graphic Design application is one of the option that can be used for beginners because it has a number of advantages and is easy to operate. In addition, it is also necessary to properly understand the communication aspect so that the content and designs created can be easily accepted and recognized by the public, as well as the legal aspects in order to avoid potential legal problems that may arise as a result of violating the provisions of the Act within the scope of Intellectual Property Rights (IPR). This training is expected to improve the skills and abilities of the participants, especially beginners, to be more creative and innovative in producing good quality content marketing and designs in a relatively easy, fast and inexpensive way. In addition, in general, it is also expected to increase the creative economy business in Indonesia. Keywords: Content Marketing, Design Grafis, Branding